Pengaruh Komunikasi Internal, Lingkungan Kerja dan Pengembangan Karir Terhadap Employee Engagement: Studi Kasus pada Karyawan PT. Suplintama Maju Semesta di Tomang, Jakarta Barat - Aris Wahyu Kuncoro; Widi Wahyudi; Rhizky Dirga Pratama; Kuncoro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The study aims to determine the effect of internal communication, work environment and career development on employee engagement in PT. Suplintama Maju Semesta at Tomang, West Jakarta. Using the Non Probability Sampling technique using the saturated method. As many as 52 employees at PT. Suplintama Maju Semesta were taken as respondents in this study. This reseacrh was conducted using multiple liniear regression methods Y = 1,144 + 0,235 X1 + 0,259 X2 + 0,267 X3 assisted by SPSS version 25 and Microsoft Excel 2016. The result showed that internal communication (X1), work environment (X2) and career development (X3) had a positve and significant effect on employee engagement (Y).